Faktor Kemiskinan Kepala Rumah Tangga Perempuan di Jawa Barat Maret 2022 - Rhida Merlian Nurazizah; Marlina, Reny Rian (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. Poverty alleviation is crucial as it significantly impacts a country's welfare, particularly within households where the head of the household is responsible for ensuring the well-being of all members. Generally, the head of the household is a man, but in certain situations, many women take on this role due to various reasons. This study aims to determine the percentage of poverty among female household heads, the factors influencing their poverty status, and the most significant predictor variable of poverty among female household heads in West Java Province in March 2022. The study uses SUSENAS March 2022 data with a sample of 3,894 female household heads, analyzed using descriptive and inferential methods (binary logistic regression). The results indicate that 95.19% of female household heads were in the non-poor category, while 4.81% were classified as poor. Factors influencing their poverty status include education level, number of household members, livable housing conditions, and education status. Among these, the number of household members (X2) has the strongest correlation with poverty status, showing that larger households tend to have a higher likelihood of being poor. These findings highlight the importance of targeted policies to improve education and living conditions for female household heads. Abstrak. Pengentasan kemiskinan sangat penting dilakukan karena kemiskinan sangat berpengaruh terhadap suatu negara. Terutama dalam rumah tangga khususnya kepala rumah tangga yang bertanggung jawab memberikan perlindungan kepada semua anggota rumah tangganya. Secara umum kepala rumah tangga adalah laki-laki, tetapi dalam kondisi tertentu banyak ditemukan kepala rumah tangga perempuan karena beberapa alasan. Sehingga tujuan penelitian ini untuk mengetahui persentase status kemiskinan kepala rumah tangga perempuan, faktor-faktor yang memengaruhi status kemiskinan kepala rumah tangga perempuan dan nilai kecenderungan terbesar pada variabel prediktor terhadap status miskin kepala rumah tangga Perempuan di Provinsi Jawa barat Maret 2022. Data yang digunakan adalah SUSENAS Maret 2022 dengan jumlah sampel 3894 kepala rumah tangga Perempuan dengan metode analisis deskriptif dan inferensial (regresi logistik biner). Kemudian hasil penelitian menunjukkan bahwa status kemiskinan di Provinsi Jawa Barat Maret 2022 kategori tidak miskin sebesar 95.19% dan kategori miskin sebesar 4.81%. Faktor-faktor yang memengaruhi status kemiskinan kepala rumah tangga Perempuan pada Maret 2022 adalah variabel pendidikan yang ditamatkan, jumlah anggota rumah tangga, rumah layak huni dan variabel status pendidikan. Nilai kecenderungan kepala rumah tangga Perempuan tertinggi terdapat pada variabel jumlah anggota rumah tangga (X2) ketegori miskin.